2018
DOI: 10.1016/j.celrep.2018.03.086
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization and Molecular Correlation of Tumor-Infiltrating Lymphocytes Using Deep Learning on Pathology Images

Abstract: SUMMARY Beyond sample curation and basic pathologic characterization, the digitized H&E-stained images of TCGA samples remain underutilized. To highlight this resource, we present mappings of tumor-infiltrating lymphocytes (TILs) based on H&E images from 13 TCGA tumor types. These TIL maps are derived through computational staining using a convolutional neural network trained to classify patches of images. Affinity propagation revealed local spatial structure in TIL patterns and correlation with overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
664
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 776 publications
(726 citation statements)
references
References 56 publications
19
664
0
3
Order By: Relevance
“…Pathological assessment of cancer specimens stained with hematoxylin and eosin (H&E) is primarily interpreted not only by tissue architecture but also by nuclear morphology of the tumor cells, which has been used for routine clinical diagnosis and computer‐aided pathological diagnosis . Recently, this field has significantly progressed to decipher clinical and biological relevance from such pathological images by combining molecular information such as genomic data …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological assessment of cancer specimens stained with hematoxylin and eosin (H&E) is primarily interpreted not only by tissue architecture but also by nuclear morphology of the tumor cells, which has been used for routine clinical diagnosis and computer‐aided pathological diagnosis . Recently, this field has significantly progressed to decipher clinical and biological relevance from such pathological images by combining molecular information such as genomic data …”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Recently, this field has significantly progressed to decipher clinical and biological relevance from such pathological images by combining molecular information such as genomic data. 14,15 Gastric cancer is one of the most common human cancers, and is the second leading cause of cancer-related deaths worldwide. 16,17 As it is often associated with chronic inflammation caused by Helicobacter pylori infection and chemicals, 18 this disease is an example of human oncogenesis that is etiologically induced by environmental factors.…”
mentioning
confidence: 99%
“…We then investigated how HE2RNA learned to recognize important histological patterns within the slides, by using our model to generate heatmaps corresponding to the most predictive tiles used to predict a gene's expression. Such approaches could also be used to detect histological subtypes 10 , genetic mutations 28 or to map the infiltration of tumors by tumor-infiltrating lymphocytes (TILs) 29 or other immune cells (e.g. macrophages, NK cells) based on cell-specific gene signatures .…”
mentioning
confidence: 99%
“…In a recent study using TCGA samples across 13 different tumour types, but not testicular cancer, it was shown that deep learning–based TIL algorithms can identify TIL patterns that are linked to molecular features and outcome 17. In this study, an average area of 70 mm 2 of the tumour was analysed with the algorithm and in average more than 100 000 cells per sample were counted, which is several orders of magnitude more than would be feasible to count through visual assessment.…”
Section: Discussionmentioning
confidence: 99%